Economic Empowerment of the People: The Effectiveness of Baznas South Kalimantan’s Zakat Community Development Program in Improving the Community’s Economic Welfare - Budi Rahmat Hakim; Dian May Syifa; Kamalia Rohana; Muhammad Noor Ridani (Muhammadiyah University of Surabaya, 2026)
This study aims to examine the effectiveness of the Zakat Community Development (ZCD) initiative implemented by Baznas South Kalimantan in improving community economic welfare. The study addresses a research gap, as limited studies analyze ZCD using the perspective of productive zakat. This research uses an empirical legal method with a qualitative approach. Data were collected through document analysis, including official reports, regulations, and related publications. The findings show that ZCD is implemented through structured stages and supported by productive activities such as fish farming, livestock, and food security programs. These activities help increase mustahik income, improve skills, and encourage economic independence. From the perspective of productive zakat, this approach reflects a shift from consumptive to empowerment-based zakat distribution. This study contributes to Islamic social finance by showing the role of productive zakat in community empowerment. The findings suggest that zakat institutions need to strengthen training, monitoring, and collaboration to ensure sustainable impacts. Keywords: Zakat Community Development, Economic Empowerment, Baznas, Mustahik, Zakat Fund Management.